Utility of patient information leaflet and perceived impact of its use on medication adherence - Majed Al Jeraisy; Heba Alshammari; Mashael Albassam; Kholoud Al Aamer; Mostafa A. Abolfotouh (BMC, 2023)
Abstract Background Although patients frequently use patient information leaflets (PILs) to obtain information about medicine, their confidence in using it may be diminished after reading it. This study aimed to assess the public perception of PIL's quality and the perceived impact of its use on medication adherence. Methods A community-based cross-sectional study of 1,138 adult individuals in Saudi Arabia, April-May 2020, was conducted via Survey Monkey using an anonymous validated e-questionnaire. Data were collected on personal characteristics, PIL readership and preferences, perception towards PIL quality and impact of its use on taking medication, and reasons for not reading PIL. In addition, logistic regression analysis was performed to identify the significant predictors of reading PIL. Significance was considered at p < 0.05. Results Nearly all participants (91.1%) reported reading PIL. The more read PIL's sections were directions of use (52.7%) and side effects (30.3%). Female gender (OR = 5.64, 95%CI: 3.53,9.02), age over 40 years (OR = 2.80, 95%CI: 1.69,4.64), and secondary education or more (OR = 1.74, 95%CI: 1.06,2.85) were the significant predictors of reading PIL. The majority of PIL readers reported their preference for verbal information (65.8%), hard copy presentation (77%), adding graphics (71.1%), and concise content of PIL (68.8%). In addition, most participants reported PIL always/usually adds to their knowledge of medicines (70.6%) and said that PIL reading positively impacted their medication adherence (64.9%). For only 8.8%, PIL reading negatively impacted their adherence, primarily because of reading information on medicine's side effects and complications (74.4%). More than one-half of participants perceived the PIL quality as good/excellent in terms of; font size (51.3%), language comprehensiveness (64.9%), paper quality (68.0%), and general appearance (64.9%). Getting sufficient information from doctors and pharmacists was the main reason for not reading the PIL (59.2%). Most participants (92.5%) agreed on standardizing how information is displayed in the PIL among all PILs of all companies. Conclusion PIL is read by nearly all the study sample, especially females, older, and educated subjects. It was perceived as beneficial in upgrading medication adherence. Effective designing of PILs should focus on patients' literacy level and age. Standardization of the PIL structure in all pharmaceutical companies is recommended.